PENDIDIKAN: SEBUAH IDE SOSIOLOGIS YANG DIKEMUKAKAN DALAM NOVEL LASKAR PELANGI KARYA ANDREA HIRATA - Hidajati, Enny; Oberto, Rachel (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
One of the sociological ideas expressed in the novel Laskar Pelangi is that there is a hidden potential in poor communities in Indonesia that needs to be raised by providing opportunities (especially education) and enough motivation and inspiration to be at the same level with Western society. This study examines the unity of the mind with elements of novel Laskar Pelangi. The approach used is the sociology of literature combined with structuralism. The three structural elements of a literary work are chosen as the focus for this research, which is the plot, the characteristic of Latitude, and the characterization of Ikal. This idea reinforces the story through unity with the plot and characterization of Ikal, and the Latitude of the Strengthening Ikal is able to express the author's sociological idea which views the importance of an opportunity and strong motivation and inspiration to uplift one's dignity.